MEDICINAL HERBS AFFECTING GONADOTROPIN HORMONES IN WOMEN:AN UPDATED SYSTEMATIC REVIEW: Pharmaceutical Sciences-Pharmacognosy - FARAHBOD, FARINAZ; HEIDARI SOURESHJANI, SAEID (International Journal of Life Science and Pharma Research, 2018)
Plants and their derivatives can exacerbate or relieve diseases such as infertility, puberty disorders, and menopause. The present - study examines the role and mechanism of medicinal plants or their products in reducing or increasing the levels of GnRH, FSH and LH in females. The key word "GnRH" or "FSH" or "Luteinizing Hormone" was searched in conjunction with the words Medicinal plant, Herb * and Phyto * in the ISI and PubMed databases (using Endnote software). Then articles related to herbs and products affecting the hormones of GnRH, FSH and LH, were included in the study, following inclusion and exclusion criteria. Plants and plant derivatives that affect fertility disorders and mainly increase GnRH, include Vitex agnus-castus, Thuja occidentalis L., Cimicifuga racemosa, Yucca schidigera, isoflavones and some Chinese herbal compounds. In some cases, plants such as Emilia coccinea decrease the fertility of the fetus by lowering the FSH and LH hormones. Also, some herbs and plant compounds are used for disorders and discontinuation of symptoms. These include isoflavones, Lepidium meyenii, Angelica gigas and Chinese herbal compounds. In some cases, Radix Ginseng and isoflavones also cause premature aging and puberty, which this issue should be taken into account for nutritional purposes. Plants and plant compounds, can cause hormonal changes, especially in female GnRH hormones mainly due to presence of having phytoestrogens and by inducing their estrogenic properties.